2022
DOI: 10.2147/nss.s351946
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Mixed Apneas in Patients with Obstructive Sleep Apnea (OSA)

Abstract: Purpose Mixed events in obstructive sleep apnea (OSA) patients (mixed-OSA) indicate respiratory regulation instability and are essential for OSA pathogenesis and prognosis. It also shows a decreased compliance with continuous positive airway pressure (CPAP). Using predictors to identify mixed-OSA has significant clinical guidance for OSA precise diagnosis and treatment. This study aimed to establish a simple and accessible method for rapid screening of mixed-OSA, thus promoting OSA precise diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, the mild high altitude itself can pose health risks, such as the development of OSAHS (11)(12)(13). Several other measures, including SpO 2 and ODI values, are important when evaluating the impact of OSAHS on a patient's health (7)(8)(9)(10). In this study, we analyzed associations between AHI levels and ODI, LSpO 2 , MSpO 2 , and TST-SpO 2 <90% values by regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the mild high altitude itself can pose health risks, such as the development of OSAHS (11)(12)(13). Several other measures, including SpO 2 and ODI values, are important when evaluating the impact of OSAHS on a patient's health (7)(8)(9)(10). In this study, we analyzed associations between AHI levels and ODI, LSpO 2 , MSpO 2 , and TST-SpO 2 <90% values by regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These assess oxygen desaturation severity during sleep and correlate with AHI ( 7–9 ). Higher AHI often means lower MSaO 2 and LSaO 2 , higher TST-SpO 2 <90%, and higher ODI, indicating more severe OSAHS ( 7 , 10 ). However, there are currently few studies exploring these metrics in high-altitude areas, especially in mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown a strong correlation between age and OSA (Ancoli-Israel et al, 1991;Liu et al, 2022), as age increases, the muscles in the nasopharynx relax and tend to collapse. Kapsimalis and Kryger (2002) found that 61.2% of people aged < 55 years had OSA, 78% of people aged > 55 years had OSA, and the prevalence of OSA increased significantly after age > 60 years.…”
Section: Agementioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a prevalent condition characterized by repeated episodes of partial or complete upper airway obstruction during sleep, leading to intermittent hypoxia and fragmented sleep [ 1 , 2 , 3 , 4 , 5 ]. While the general population is at risk, pregnant women are particularly susceptible due to physiological changes that occur during pregnancy, such as weight gain and edema that can exacerbate airway collapsibility, as well as hormonal fluctuations that may affect respiratory drive and muscle tone [ 6 , 7 ]. In addition, the growing fetus and the associated increase in body mass can lead to mechanical pressure on the respiratory system [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%